PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PENGGUNAAN E – WALLET - Listyawati, Liling; Subardini, Subardini (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
This research aims to determine the effect of brand image and promotion on the decision to use e-money shop for Dr. Soetomo Surabaya both simultaneously and partially as well as to determine the dominant variable on the use decision e - money shopepay. This research is a quantitative research with a causal research method. The population in this study were all Dr. university students. Soetomo, who has the Shopeepay application and has made transactions using Shopeepay, has a total sample of 96 respondents who have been distributed through questionnaires. This study used a random sampling technique to collect respondents and used the unknown populations formula in determining the sample because the population of this study was unknown. Furthermore, the data analysis used instrument test, classical assumption test, multiple linear regression analysis test, simultaneous test, partial test, and determination coefficient test. The results of this study indicate that brand image and promotion have an effect both simultaneously and partially on the decision to use Shopeepay e-money and promotion is the dominant variable influencing the decision to use e-money Shopeepay.